The effectiveness of beetroot extract (Beta vulgaris L.) on thermoplastic nylon denture base wearers in inhibiting the growth of Streptococcus mutans: Efektivitas ekstrak buah bit (Beta vulgaris L.) pada pemakai basis gigi tiruan nilon termoplastik dalam menghambat pertumbuhan Streptococcus mutans - Kadek Dwi Dessy Sapitri; Ria Koesoemawati (Makassar Dental Journal, 2023)
Thermoplastic nylon is a denture base that is in high demand by dentists because it has several advantages over acrylic resin materials. Streptococcus mutans is one of the bacteria that can cause the formation of dental plaque and halitosis. Beetroot (Be-ta vulgaris L.) is a natural ingredient as an anti-inflammatory that contains phenol compounds, flavonoids, saponins, tannins, and betalains. Through this study, the effectiveness of beetroot extract on thermoplastic nylon denture users against the growth of S.mutans was determined. The experimental laboratory study used Fittydent® as positive control and sterile distilled water as negative control. Based on one-way Anova test, there was no significant difference between 10% and 40% beetroot extract (p>0.05). Immersion of thermoplastic nylon plates in 10% and 40% beetroot extract had an effect on the growth of S.mutans bacteria. This is due to the nature of thermoplastic nylon which easily absorbs water and phenol compounds contained in beet-root extract by diffusion. It is concluded that beetroot extract has the effectiveness in inhibiting the growth of S.mutans on ther-moplastic nylon plates.